2009
DOI: 10.1111/j.1365-294x.2009.04366.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of selection, as measured by single nucleotide polymorphism variation, is dependent on inbreeding rate in Drosophila melanogaster

Abstract: It is often hypothesized that slow inbreeding causes less inbreeding depression than fast inbreeding at the same absolute level of inbreeding. Possible explanations for this phenomenon include the more efficient purging of deleterious alleles and more efficient selection for heterozygote individuals during slow, when compared with fast, inbreeding. We studied the impact of inbreeding rate on the loss of heterozygosity and on morphological traits in Drosophila melanogaster. We analysed five noninbred control li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…This suggests that, in our lines, purging is not more efficient with slower rates of inbreeding. A study of 40 SNP markers showed that our slow inbred lines actually maintain higher levels of molecular variation compared to fast inbred lines despite the same expected level of inbreeding (Demontis et al 2009). This is interesting as it emphasizes that selection acts differently in slow and fast inbred lines.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that, in our lines, purging is not more efficient with slower rates of inbreeding. A study of 40 SNP markers showed that our slow inbred lines actually maintain higher levels of molecular variation compared to fast inbred lines despite the same expected level of inbreeding (Demontis et al 2009). This is interesting as it emphasizes that selection acts differently in slow and fast inbred lines.…”
Section: Discussionmentioning
confidence: 85%
“…Several interesting results and analyses have been presented in this line (Kristensen and Sorensen, 2005;Demontis et al, 2009;Ayroles et al, 2009;Paige, 2010;Vermeulen et al, 2013).…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 88%
“…According to most researchers, inbreeding leads to reduced heterozygosity and respectively, lower genetic diversity of populations (Falconer and Mackay, 1996;Кeller, 2002;Charlesworth and Willis, 2009;Nietlisbach et al, 2016;Tanchev, 2016). Some studies and analyses however provide evidence that the process of inbreeding-induced reduction of heterozygous genotypes within a population is multifactorial, although the most influential factors are its size, heterogeneity and the rate of achieving a specific inbreeding level (Maiwashe and Blackburn, 2004;Frankham, 2002;Charlesworth and Charlesworth, 1999;Demontis et al, 2009;Liao and Reed, 2009). Hence, the main purpose of the present study was to investigate the genetic C/T variability of the growth hormone (GH) gene in outbred New Zealand White and inbred synthetic populations of rabbits through PCR-RFLP.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%
“…Moreover, although assisted translocation of entire species may be difficult, translocation of genotypes adapted to different conditions is likely to be much more feasible and might provide an insurance policy against future change (Broadhurst et al 2008, Hedrick & Fredrickson 2010, but see Bijlsma et al 2010. In this regard, assessments of movements of individuals into areas perhaps already occupied by other populations of the species may have to move away from the consideration of neutral markers only (which will show differences based mostly on time of isolation) and consider genes that are likely to have significance in the context of environmental responses (Demontis et al 2009, Pertoldi et al 2010. Genome-based evolutionary physiology has much to offer here too.…”
Section: Conservation Implicationsmentioning
confidence: 99%